We will learn how to find the position of a point with respect to a circle.
A point (x\(_{1}\), y\(_{1}\)) lies outside, on or inside a circle S = x\(^{2}\) + y\(^{2}\) + 2gx + 2fy + c = 0 according as S\(_{1}\) > = or <0, where S\(_{1}\) = x\(_{1}\)\(^{2}\) + y\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c.
Let P (x\(_{1}\), y\(_{1}\)) be a given point, C (-g , -f) be the centre and a be the radius of the given circle.
We need to find the position of the point P (x\(_{1}\), y\(_{1}\)) with respect to the circle S = x\(^{2}\) + y\(^{2}\) + 2gx + 2fy + c = 0.
Now, CP = \(\mathrm{\sqrt{(x_{1} + g)^{2} + (y_{1} + f)^{2}}}\)
Therefore, the point
(i) P lies outside the circle x\(^{2}\) + y\(^{2}\) + 2gx + 2fy + c = 0 if CP > the radius of the circle.
i.e., \(\mathrm{\sqrt{(x_{1} + g)^{2} + (y_{1} + f)^{2}}}\) > \(\mathrm{\sqrt{g^{2} + f^{2} - c}}\)
⇒ \(\mathrm{(x_{1} + g)^{2} + (y_{1} + f)^{2}}\) > g\(^{2}\) + f\(^{2}\) - c
⇒ x\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + g\(^{2}\) + y\(_{1}\)\(^{2}\) + 2fy\(_{1}\) + f\(^{2}\) > g\(^{2}\) + f\(^{2}\) – c
⇒ x\(_{1}\)\(^{2}\) + y\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c > 0
⇒ S\(_{1}\) > 0, where S\(_{1}\) = x\(_{1}\)\(^{2}\) + y\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c.
(ii) P lies on the circle x\(^{2}\) + y\(^{2}\) + 2gx + 2fy + c = 0 if CP = 0.
i.e., \(\mathrm{\sqrt{(x_{1} + g)^{2} + (y_{1} + f)^{2}}}\) = \(\mathrm{\sqrt{g^{2} + f^{2} - c}}\)
⇒ \(\mathrm{(x_{1} + g)^{2} + (y_{1} + f)^{2}}\) = g\(^{2}\) + f\(^{2}\) - c
⇒ x\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + g\(^{2}\) + y\(_{1}\)\(^{2}\) + 2fy\(_{1}\) + f\(^{2}\) = g\(^{2}\) + f\(^{2}\) – c
⇒ x\(_{1}\)\(^{2}\) + y\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c = 0
⇒ S\(_{1}\) = 0, where S\(_{1}\) = x\(_{1}\)\(^{2}\) + y\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c.
(iii) P lies inside the circle x\(^{2}\) + y\(^{2}\) + 2gx + 2fy + c = 0 if CP < the radius of the circle.
i.e., \(\mathrm{\sqrt{(x_{1} + g)^{2} + (y_{1} + f)^{2}}}\) < \(\mathrm{\sqrt{g^{2} + f^{2} - c}}\)
⇒ \(\mathrm{(x_{1} + g)^{2} + (y_{1} + f)^{2}}\) < g\(^{2}\) + f\(^{2}\) - c
⇒ x\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + g\(^{2}\) + y\(_{1}\)\(^{2}\) + 2fy\(_{1}\) + f\(^{2}\) < g\(^{2}\) + f\(^{2}\) – c
⇒ x\(_{1}\)\(^{2}\) + y\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c < 0
⇒ S\(_{1}\) < 0, where S\(_{1}\) = x\(_{1}\)\(^{2}\) + y\(_{1}\)\(^{2}\) + 2gx\(_{1}\) + 2fy\(_{1}\) + c.
Again, if the equation of the given circle be (x - h)\(^{2}\) + (y
- k)\(^{2}\) = a\(^{2}\) then the coordinates of the centre C (h, k) and the radius of the circle
= a
We need to find the position of the point P (x\(_{1}\), y\(_{1}\)) with respect to the circle (x - h)\(^{2}\) + (y - k)\(^{2}\)= a\(^{2}\).
Therefore, the point
(i) P lies outside the circle (x - h)\(^{2}\) + (y - k)\(^{2}\) = a\(^{2}\) if CP > the radius of the circle
i.e., CP > a
⇒ CP\(^{2}\) > a\(^{2}\)
⇒ (x\(_{1}\) - h)\(^{2}\) + (y\(_{1}\) - k)\(^{2}\) > a\(^{2}\)
(ii) P lies on the circle (x - h)\(^{2}\) + (y - k)\(^{2}\) = a\(^{2}\) if CP = the radius of the circle
i.e., CP = a
⇒ CP\(^{2}\) = a\(^{2}\)
⇒ (x\(_{1}\) - h)\(^{2}\) + (y\(_{1}\) - k)\(^{2}\) = a\(^{2}\)
(iii) P lies inside the circle (x - h)\(^{2}\) + (y - k)\(^{2}\) = a\(^{2}\) if CP < the radius of the circle
i.e., CP < a
⇒ CP\(^{2}\) < a\(^{2}\)
⇒ (x\(_{1}\) - h)\(^{2}\) + (y\(_{1}\) - k)\(^{2}\) < a\(^{2}\)
Solved examples to find the position of a point with respect to a given circle:
1. Prove that the point (1, - 1) lies within the circle x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4 = 0, whereas the point (-1, 2) is outside the circle.
Solution:
We have x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4 = 0 ⇒ S = 0, where S = x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4
For the point (1, -1), we have S\(_{1}\) = 1\(^{2}\) + (-1)\(^{2}\) - 4 ∙1 + 6 ∙ (- 1) + 4 = 1 + 1 - 4 - 6 + 4 = - 4 < 0
For the point (-1, 2), we have S\(_{1}\) = (- 1 )\(^{2}\) + 2\(^{2}\) - 4 ∙ (-1) + 6 ∙ 2 + 4 = 1 + 4 + 4 + 12 + 4 = 25 > 0
Therefore, the point (1, -1) lies inside the circle whereas (-1, 2) lies outside the circle.
2. Discuss the position of the points (0, 2) and (- 1, - 3) with respect to the circle x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4 = 0.
Solution:
We have x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4 = 0 ⇒ S = 0 where S = x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4
For the point (0, 2):
Putting x = 0 and y = 2 in the expression x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4 we have,
S\(_{1}\) = 0\(^{2}\) + 2\(^{2}\) - 4 ∙ 0 + 6 ∙ 2 + 4 = 0 + 4 – 0 + 12 + 4 = 20, which is positive.
Therefore, the point (0, 2) lies within the given circle.
For the point (- 1, - 3):
Putting x = -1 and y = -3 in the expression x\(^{2}\) + y\(^{2}\) - 4x + 6y + 4 we have,
S\(_{1}\) = (- 1)\(^{2}\) + (- 3)\(^{2}\) - 4 ∙ (- 1) + 6 ∙ (- 3) + 4 = 1 + 9 + 4 - 18 + 4 = 18 - 18 = 0.
Therefore, the point (- 1, - 3) lies on the given circle.
● The Circle
11 and 12 Grade Math
From Position of a Point with Respect to a Circle to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Feb 24, 24 04:33 PM
Feb 24, 24 04:11 PM
Feb 24, 24 04:10 PM
Feb 24, 24 04:09 PM
Feb 24, 24 10:59 AM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.